A Study on the Improvement of Structural Performance by Glass Fiber-Reinforced Polyurea (GFRPU) Reinforcement - Jun-Hyeok Song; Eun-Taik Lee; Hee-Chang Eun (Advances in Civil Engineering)
Polyurea has a high tensile strength, elongation, and the capability to absorb the energy generated by dynamic and impulsive blast loading. Glass fibers are a reinforcement material for repairing and retrofitting the concrete members. The polyurea provides ductility, and the fibers provide improved stiffness and strength to the composite system. Glass-fiber reinforced polyurea (GFRPU) is a composite of polyurea and fibers and is applied as a reinforcement through a simple spraying method. GFRPU coating has a simple construction, and unlike existing strengthening methods such as fiber-reinforced polymer (FRP) or a steel plate, it prevents a debonding from the concrete surface. Seven beams of one externally nonreinforced concrete beam and six concrete beams with and without a reinforcing bar are tested using the thickness of the spray and the number of coating faces. The applicability of GFRPU was investigated through the experiments, and the test results indicate that the GFRPU strengthening method is feasible for enhancing the load-carrying capacity and flexural ductility.